STUDENTS' PERCEPTIONS TOWARD THE USE OF BLENDED LEARNING IN TEACHING ENGLISH OF ENGLISH EDUCATION DEPARTMENT STUDENTS AT UIN ALAUDDIN MAKASSAR - Siti Juhairiyah; Mardiana; Sitti Nurpahmi; Nur Aliyah Nur (elstic : english language linguistics culture, 2022)
The purpose of this research is to find out students’ perception toward the use of blended learning. The research question of this research was “what is the students’ perceptions toward the use of blended learning in teaching English at the English Education Students in UIN Alauddin Makassar?”. The research sample and population are the English Education Department students with total number of populations were 98 students.This research applied a quantitative method with survey design, using total sampling where the data collected with online questionnaires. The questionnaires were formed by the researcher, using theories from some experts such as a theory about the learners’ knowledge by (Macdonald, 2008), a theory about the effectiveness of blended learning and theories about the benefits of blended learning by (Debra and John, 2010) and (Brown in Buket and Meryem, 2008). The data was analyzed by using the frequencies of Likert Scale and finding the mean score. The findings showed that the highest percentage of students’ response on the students’ perception toward the use of blended learning in teaching English was in the statement 9 namely “I like to learn at my own phase, that is why blended learning is interesting” with 82.24% which is from the effectiveness of blended learning, one of the aspects of question that are included in the questionnaires. And the lowest percentage was in the statement 18 namely “There is no difference between blended learning and any other methods” with 34.69% which also is the same aspect of question as the highest percentage, but was a unfavorable statement. Based on the research findings, the majority of students gave positive responses toward the use of blended learning in teaching English from the aspect of the effectiveness of blended learning itself and the mean score of students’ perceptions toward the use of blended learning was 3.47 which came from 67 positive responses.